2013
DOI: 10.1128/jvi.00533-13
|View full text |Cite
|
Sign up to set email alerts
|

Activity Increase in Respiratory Chain Complexes by Rubella Virus with Marginal Induction of Oxidative Stress

Abstract: bMitochondria are important for the viral life cycle, mainly by providing the energy required for viral replication and assembly. A highly complex interaction with mitochondria is exerted by rubella virus (RV), which includes an increase in the mitochondrial membrane potential as a general marker for mitochondrial activity. We aimed in this study to provide a more comprehensive picture of the activity of mitochondrial respiratory chain complexes I to IV. Their activities were compared among three different cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 51 publications
0
44
0
Order By: Relevance
“…Thus possibly some of the remaining nuclear-encoded complex III subunit(s) may be affected by LACE1/Afg1 deficiency. The markedly increased activity of complex II is frequently encountered in systems with respiratory chain deficiency where it is thought to serve as a compensatory mechanism for maintaining optimal electron flow through the chain [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus possibly some of the remaining nuclear-encoded complex III subunit(s) may be affected by LACE1/Afg1 deficiency. The markedly increased activity of complex II is frequently encountered in systems with respiratory chain deficiency where it is thought to serve as a compensatory mechanism for maintaining optimal electron flow through the chain [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, in states of ‘mitochondrial hyperactivity’ (in which ETC activities are upregulated), the ETC generates pathologically high ΔΨ m levels, and this mitochondrial hyperpolarization leads to an exponential increase in ROS generation at membrane potentials exceeding 140 mV. This has been demonstrated in many pathologies, including lupus erythematosus (Doherty et al, 2014), rubella infection (Claus et al, 2013) and in multiple sclerosis lesions (Mahad et al, 2009). mRNA levels of Cox1 , one of the three mitochondrially encoded subunits of complex IV of the ETC (Heilbronn et al, 2007), was also upregulated in the skeletal muscle of aged recuperated offspring.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently suggested that the respiratory chain complexes are not arranged simply in a linear order of enzymatic complexes. These complexes display different activities toward one another [74]. Subunits of respiratory complexes differ in their correlation between protein expression and enzymatic activity [75].…”
Section: Discussionmentioning
confidence: 99%